2000
DOI: 10.1097/00000542-200002000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine Facilitates Inhibitory Transmission in Substantia Gelatinosa of Adult Rat Spinal Cord (Part 1)

Abstract: These results suggest that norepinephrine enhances inhibitory synaptic transmission in the substantia gelatinosa through activation of presynaptic alpha1 receptors, thus providing a mechanism underlying the clinical use of alpha1 agonists with local anesthetics in spinal anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(101 citation statements)
references
References 36 publications
8
91
1
1
Order By: Relevance
“…Moreover, the actions of NA that we observed in the AOB are reminiscent of NA action in other brain regions and spinal cord. Most prominently, NA facilitates GABAergic transmission in stellate cells of the cerebellum (Llano and Gerschenfeld, 1993;Kondo and Marty, 1998), amygdala (Braga et al, 2004), sensorimotor cortex (Bennett et al, 1998), ventral bed nucleus of the stria terminalis (Dumont and Williams, 2004), and hypothalamus in the brain and in the substantia gelatinosa of the spinal cord (Baba et al, 2000). In our studies, the increase in mIPSC frequency was mediated by activation of ␣1 adrenergic receptors.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, the actions of NA that we observed in the AOB are reminiscent of NA action in other brain regions and spinal cord. Most prominently, NA facilitates GABAergic transmission in stellate cells of the cerebellum (Llano and Gerschenfeld, 1993;Kondo and Marty, 1998), amygdala (Braga et al, 2004), sensorimotor cortex (Bennett et al, 1998), ventral bed nucleus of the stria terminalis (Dumont and Williams, 2004), and hypothalamus in the brain and in the substantia gelatinosa of the spinal cord (Baba et al, 2000). In our studies, the increase in mIPSC frequency was mediated by activation of ␣1 adrenergic receptors.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, we found that NA increased sEPSC through α1 receptors in some populations of regular type neurons. Several studies have addressed the relevance of NAergic modulation of synaptic events in the spinal cord (1,2,5,20,29). In this study, α2 receptor-mediated synaptic inhibition of sEPSC was observed in both types of neurons, consistent with previous reports.…”
Section: Synaptic Current Modulation Of Nasupporting
confidence: 91%
“…Presynaptic actions of NA: To address whether spinally administered NA acts presynaptically to alter the excitatory and inhibitory transmitter release and, if so, to identify which receptor subtype is involved, a blind patch-clamp technique to study the action of NA on miniature excitatory and inhibitory postsynaptic currents (mEPSCs and mIPSCs, respectively) in SG neurons from adult rat spinal cord slices was made (45,63,64). In the majority of SG neurons, NA dosedependently increased the frequency of GABAergic and glycinergic mIPSCs, while mEPSCs are not significantly altered in the presence of tetrodotoxin (TTX).…”
Section: Electrophysiological Study 1) In Vitro Studymentioning
confidence: 99%
“…These results indicate that NA enhances inhibitory transmitter release on the SG through the activation of presynaptic α 1 receptors, thus providing a mechanism underlying the clinical use of α 1 agonists with local anesthetics in spinal anesthesia. Baba et al (64) further addressed the action of NA on the somatodendritic sites or the terminals of inhibitory interneurons, in particular GABAergic ones. NA causes an increase in not only the frequency but also the amplitude of GABAergic IPSCs.…”
Section: Electrophysiological Study 1) In Vitro Studymentioning
confidence: 99%
See 1 more Smart Citation